An In vitro Comparative Analysis of the Shear Bond Value of Sixth, Seventh and Eight Generation Dentin Bonding Agents - Prashant Jalannavar; Suresh Kumar Kalgapure; Vijay Parmar; Sopan Singh; Ashtha Arya; Karishma Dudekula; Kanika S. Dhull (Journal of Pharmacy and Bioallied Sciences)
Objective: This study evaluates the shear bond strength (SBS) of 6th, 7th, and 8th generation dentin bonding agents. Materials and Methods: Thirty extracted premolars were divided into three groups of 10. Group A used a 6th generation bonding agent, Group B a 7th generation bonding agent, and Group C a 8th generation bonding agent. Each tooth was fixed in acrylic resin, sectioned to expose dentin, treated with the respective bonding agent, and built up with composite resin. SBS was assessed by universal testing machine. Results: Highest shear bond value was illustrated by the 8th generation bonding agent, with subsequent values progressively lower for the 7th and 6th generation bonding agents. Conclusion: The 8th generation bonding agents exhibit superior shear bond strength, suggesting enhanced dental restoration durability. Further clinical validation is recommended.